CO2 Fixation and PCHC Depolymerization by a Dinuclear β‐Diketiminato Zinc Complex. Issue 2 (20th December 2022) - Liao, Xi; He, Jiang‐Hua; Zhang, Yue‐Tao
Abstract: The production of cyclic carbonates and (or) polycarbonates from the coupling of carbon dioxide (CO2 ) with epoxides is a practical strategy for CO2 fixation. Chemically recycling of the polycarbonates is also urgently needed for sustainable development of plastics. Here a dinuclear β ‐diketiminato (BDI) methyl zinc complex((BDI‐ZnMe)2, 1 ) is reported to achieve not only selective cyclic carbonates from cycloaddition of CO2 to meso ‐CHO in the presence of cocatalyst, but also effective depolymerization of PCHC into trans ‐CHC. The trans ‐CHC can be further transformed into cis ‐CHC, thus demonstrating great application potentials of this strategy in CO2 fixation and chemical recycling of plastics. Abstract : The coupling of CO2 with meso ‐CHO to cis‐ CHC and PCHC, depolymerization of PCHC to trans ‐CHC, and transformation of trans ‐CHC into cis ‐CHC, can be achieved by BDI methyl zinc complex under different reaction conditions.